Carbon management strategies in manufacturing companies: An exploratory note - Simon Cadez; Albert Czerny (Journal for East European Management Studies, 2010)
In order to meet the Kyoto Protocol's greenhouse gas emissions targets, the EU has implemented an Emissions Trading Scheme (EU ETS) as a cornerstone of its climate policy. The main attribute of this mechanism is its inherent flexibility. It offers companies the possibility of tailoring a carbon management strategy that is the most cost-effective, i.e. reducing actual emissions vs. buying allowances to emit. Although the EU ETS was launched in 2005, to date little is known about its implications for corporate carbon management. The study provides some original insights into corporate carbon management strategies by deploying a case study of two Slovenian manufacturing companies. – – Um die Ziele des Kyoto-Protokolls bezüglich Treibhausgasemissionen zu erreichen, hat die EU ein Emissionshandelsschema (EUETS) als Eckstein seiner Klimapolitik eingeführt. Die wichtigste Eigenschaft dieses Mechanismus ist die inherente Flexibilität. Es bietet den Unternehmen die Möglichkeit der Anpassung ihrer Kohlenstoffmanagement-Strategie, das heisst die Verringerung der tatsächlichen Emissionen oder der Kauf von entsprechenden Zertifikaten. Obwohl die EUETS im Jahr 2005 eingeführt wurde, ist bis heute nur wenig über ihre Bedeutung für das betriebliche Kohlenstoffmanagement bekannt. Diese Studie liefert einige Einblicke in betriebliche Kohlenstoffmanagement-Strategie anhand einer Fallstudie von zwei slowenischen Industrieunternehmen.
Keywords: 650; Carbon management; Strategy; EU Emissions Trading Scheme; Carbon efficiency; Slovenia